'Family matters': Ageing and the intergenerational social contract in urban Ahmedabad, Gujarat. (October 2017) - Gangopadhyay, Jagriti; Samanta, Tannistha
This article aims to understand the complex interactions of family and intergenerational relationships in an emerging city in India. Demographic work on population ageing in India has primarily focused on family structure, health outcomes and institutional living. Though the focus of these studies has been on the Indian family, surprisingly, an in-depth study of the complex dialectic of the intergenerational relationships is often missing from the gerontological literature. Drawing from in-depth qualitative interviews in the city of Ahmedabad, Gujarat, this article unsettles the assumptions around filial obligation and intergenerational support. In particular, the study shows that the intergenerational social contract is mediated by the economic dependence of the ageing parents on their adult children. Our observations lend support to the construct of ambivalence (coexistence of conflict and affection) that is suggested by the dominant social-psychological paradigm of intergenerational solidarity-conflict. Additionally, the article underscores cultural meanings of identity, gender ideology and role continuity among older Indians.